Relevancy of accountıng ınformatıon under ıfrs at borsa ıstanbul (BIST) ın successıve fınancıal perıods - Al-Ashı, Mohammed (My University, 2016)
BORSA ISTANBUL(BIST) ŞİRKETLERİNİN UFRS’YE GÖRE HAZIRLANMIŞ MUHASEBE BİLGİLERİNİN BİRBİRİRİNİ TAKİP EDEN DÖNEMLERDEKİ İLGİLİLİĞİ Bu çalışma, Borsa Istanbul’da işlem gören imalat sanayi firmalarının muhasebe bilgilerinin ilgililiğini ölçmeyi amaçlamaktadır. Çalışmada, stok, sabit kıymetler ve alacak kalemlerinin öngörü yetisi, ARIMA modeli kullanılarak ölçülmüştür. Sonuçlar, UFRS göre yapılan düzenlemenin öngörü düzeyini iyileştirdiğini göstermemiştir. Ayrıca, seçilen muhasebe kalemleri ve hisse fiyatı arasındaki ilişkide UFRS düzenlenmesinden sonra bir iyileşme gözlemlenmiştir. Diğer yandan, iki farklı veri seti kullanılarak, her bir muhasebe kalemi için çoklu regresyon modeli uygulandığında (yıllık ve firma veriler ile) yine, UFRS uygulamasından sonra herhangi bir iyileşme gözlemlenmemiştir. Bu çalışmanın katkısını konvansiyonel metot ile karşılaştırmak için özsermaye defter değeri ile şirket karının hisse fiyatını açıklama gücü bir regresyon modeli kullanılarak ölçülmüştür. Kesitsel analizin sonucuna göre, muhasebe bilgilerinin ilgililiği UFRS’nin uygulanmasından sonra göstermemektedir. Ancak, üç aylık veriler kullanıldığında, UFRS uygulamasından sonra ilgililik düşmektedir. Bu çalışma ilgililiği her bir şirketin kendi yıllık verisi ile ölçmektedir. Sonuçlar, UFRS uygulamasının öncesinde ve sonrasında önemli farklılıklar göstermemektedir. Farklı veri setlerini inceleyen konvansiyonel modele ve seçilen muhasebe kalemleri ile hisse fiyatı ve bazı bağımsız değişkenler arsındaki ilişkiyi ölçen ARIMA modeline göre, UFRS uygulamasının muhasebe bilgilerinin ilgililiğinde ve öngörü yetisinde herhangi bir iyileştirme sağlamadığı sonucuna ulaşılmıştır. UFRS, Borsa Istanbul, ARIMA, Firma ilgililiği

RELEVANCY OF ACCOUNTING INFORMATION UNDER IFRS AT BORSA ISTANBUL (BIST) IN SUCCESSIVE FINANCIAL PERIODS This study aims to measure the relevancy of accounting information at the manufacturing firms listed in Borsa Istanbul. To achieve the objectives of this study, chosen accounting elements; Inventory, Property, plant, and equipment, and Accounts receivable, were examined for predictability by the ARIMA model and the results show that predictability did not improve after the adoption of IFRS. In addition, according to the measurement of the relationship between the chosen accounting elements and stock price, there are significant improvements detected after the adoption of IFRS. Furthermore, when a multiple regression model is applied for each accounting element separately using two different sets of data; annual pooled and separate for each firm, no improvements are detected after the adoption of IFRS. To compare the contribution of this study with the conventional methodology, a regression model is applied to measure the explanatory power of book values of equity and earnings to explain stock prices. The result of the cross sectional analysis shows that the relevancy of accounting information increases insignificantly after the adoption of IFRS. But when quarterly data is used, the result shows that the relevancy declines after the adoption of IFRS. In addition, this study measures relevancy by using annual and separate data for each firm. The results show that there are no significant differences between the pre and post adoption of IFRS periods. According to the use of the conventional model that examined relevancy for different sets of data, as well as the examination of predictability by ARIMA, the examination of the relationship between the chosen accounting elements and stock price, and the examination of the relationship between the chosen accounting elements and some chosen independent variables, it could be concluded that the adoption of IFRS did not cause any significant improvements on relevancy nor predictability of accounting information. Key words: Relevancy, IFRS, Borsa Istanbul, ARIMA, Firms relevancy
Keywords: Finansal tablolar; Muhasebe; UFRS; Yönetim